A Study on the Internal Audit Performance in Fraud Detection in Private Enterprises in the State of Sao Paulo - Pereira, Anisio Candido (2007)
Internal Audit is the countable specialization directed to test the effectiveness of the operational and countable controls implanted by the administration, with the purpose to restrain the processes of errors and frauds in the organizations. Nowadays the great amount of fraudulent scandals in the countable and financial areas of the companies leads to a reflection about the role and the effectiveness of this department in the processes of detention of frauds.  It is stressed that frauds can occur in the countable environment, financial, of internal and ethical control. In this way the article considers an empirical research in order to put into evidence the effectiveness of the Internal Auditorship in the processes of detention of frauds. As a conclusion, the article emphasizes the importance of the auditing tools and procedures in the task of detecting frauds as well as the effectiveness of internal auditors in such type of work. Key-words: Internal audit. Frauds.  Audit procedures.